Pengaruh Brand Image dan After-Sales Service Terhadap Purchase Intention Pada Showroom Mobil Jeix Autodeals - Jayanata, Rido; Warganegara, Tri Lestira (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
The rapid growth of Indonesia’s automotive industry has contributed to the rising opportunities in the used car sales sector. Jeix Autodeals, a used car showroom based in Metro City, Lampung, faces challenges in maintaining stable sales. Preliminary observations indicate that brand image and after-sales service play a critical role in shaping consumer purchase intention. This study aims to examine the influence of brand image and after-sales service on purchase intention, both partially and simultaneously. The research employed a quantitative method using multiple linear regression analysis. Data were collected from 100 respondents who have purchased or intended to purchase used cars in Lampung Province. The results show that brand image has a positive and significant effect on purchase intention, with a t-value of 5.614 > t-table 1.984 and a significance value of 0.000 < 0.05. Similarly, after-sales service also has a positive and significant impact, with a t-value of 5.181 and significance of 0.000. Simultaneous testing revealed that both variables significantly influence purchase intention with an F-value of 45.736 > F-table 2.70 and a significance of 0.000. The coefficient of determination indicates that 48.5% of the variation in purchase intention is explained by brand image and after-sales service. These findings highlight the importance of building a strong brand image and providing responsive after-sales service to enhance consumer purchasing decisions in the used car market.